LECTURERS’ PERCEPTION TOWARD BASIC READING TEXTBOOK IN STKIP PGRI SUMATERA BARAT - Rozman, Febby Carmila; Sesmiyanti, Sesmiyanti; Suharni, Suharni (TELL - US JOURNAL, 2020)
This study aims to describe the lecturers' perception of the Basic Reading textbook used in the Basic Reading Course. This study used a qualitative approach with a total of 2 respondents. The data collection technique used semi-structured interviews with 2 English Education Study Program lecturers at STKIP PGRI Sumatera Barat. The results of this study explained that lecturers' perception toward Basic Reading textbook was based on four main components of the Basic Reading textbook, namely: content, vocabulary and grammar, exercises and activities and as well as the attractiveness and physical make up of the textbook. The lecturers' perception of the content of the textbook was very helpful for students in understanding learning. Regarding vocabulary and grammar in the Basic Reading textbook, according to the lecturer who used the Basic Reading textbook, the used of vocabulary and grammar was easy to understand and in accordance with student abilities. The activities used have an effect on students in implementing character education in the learning process. Exercises also required students to think critically. The attractiveness and physical make up of the textbook showed that the textbook cover and pictures on the textbook were very attractive to students because the textbook components are based on Multimodality. Multimodality is a combination of elements such as visual design, pictures, writing variations, layout, utterance, diagrams and tables and more.